2021
DOI: 10.2174/1570159x19666210608165509
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Caffeic Acid Phenethyl Ester (CAPE) in CNS Disorders: Mechanistic and Therapeutic Insights

Abstract: : Neurological disorders like Alzheimer’s disease (AD), Parkinson’s disease (PD), stroke, amyotrophic lateral sclerosis, Huntington’s disease (HD), epilepsy, traumatic brain injury (TBI), depression and anxiety are responsible for thousands of deaths worldwide every year. With the increase in life expectancy, there has been a rise in the prevalence of these disorders. Age is one of the major risk factors for these neurological disorders and with the aged population is set to rise to 1.25 billion by 2050. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…Intranigral MPTP injection has been shown in the earlier reports to induce PD by selective loss of dopaminergic neurons. It has been further reported that MPTP also reduces the TH expression and subsequently leads to motor and cognitive de cits in rats [41,25,23,24,42]. Our data is consistent with these reports of the MPTP administration, which have also shown a reduction in the open eld and rotarod performance in the rodent model of PD.…”
Section: Discussionsupporting
confidence: 93%
“…Intranigral MPTP injection has been shown in the earlier reports to induce PD by selective loss of dopaminergic neurons. It has been further reported that MPTP also reduces the TH expression and subsequently leads to motor and cognitive de cits in rats [41,25,23,24,42]. Our data is consistent with these reports of the MPTP administration, which have also shown a reduction in the open eld and rotarod performance in the rodent model of PD.…”
Section: Discussionsupporting
confidence: 93%
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
“…Based on literature data mining, flavonoid‐glycosides and terpenes in G. biloba are the main components of its pharmacological activities such as anti‐inflammatory, antioxidant, blood circulation‐improving, and platelet anti‐aggregatory activities 22–51 . Therefore, the above ingredients were selected for the study of the active ingredients of GBE against IS, as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Caffeic acid phenyl ester (CAPE), an antioxidative compound abundant in honeybee propolis, was shown to have beneficial effects against neuronal injuries [ 60 ]. In a recent study examining the effects of CAPE on AD pathology and cognitive functions in AβO-injected mice [ 61 ], CAPE, intraperitoneally administered for 10 days, significantly reversed spatial memory impairment, measured using the MWM test.…”
Section: Small Molecules With Protective Activity Against Aβo Neurotoxicitymentioning
confidence: 99%